The spectrum of p53 mutations in colorectal adenomas differs from that in colorectal carcinomas. Issue 6 (1st June 2002) - Hao, X P; Frayling, I M; Sgouros, J G; Du, M Q; Willcocks, T C; Talbot, I C; Tomlinson, I P M
Abstract : Background: p53 mutations are frequently observed in colorectal carcinomas but they have also been found in colorectal adenomas, although considerably less frequently. Aims: To explore p53 mutations in benign tumours, we have screened 70 colorectal adenomas for allelic loss at, and point mutations in, TP53 by analysis of selected microdissected cell populations. Results: Sixteen (22.8%) adenomas were found to have allelic loss, of which 11 (15.7%) had p53 mutations. In adenomas with mild, moderate, or severe dysplasia, mutation or allelic loss occurred in 4.8%, 16.7%, and 52.6%, respectively (p<0.001). Seven different mutations were found, all missense changes or inframe deletions: one (Thr150Arg) has not been found before while three (Gln144His, Gly245Arg, and Glu285Gln) have not been described previously in colorectal tumours. The other three mutations (Arg175Gly, ΔPro190, and Gly245Ser) have been found in colorectal carcinomas, the last commonly. Adenomas harboured a spectrum of p53 mutations which was significantly different from cancers as regards the position in the gene and a higher frequency of G→C/C→G changes. Conclusions: Combining our data on adenomas with data already published and in comparison with the spectrum of mutations in colorectal carcinomas, it is suggested that some p53 mutations have a weaker effect than others and are therefore more likely to be found in adenomas which have not progressed to carcinomas.